TLR4-activated microglia require IFN-γ to induce severe neuronal dysfunction and death in situ - Papageorgiou, Ismini E.; Lewen, Andrea; Galow, Lukas; Cesetti, Tiziana; Scheffel, Jörg; Regen, Tommy; Hanisch, Uwe-Karsten; Kann, Oliver (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Microglia (tissue-resident macrophages) represent the main cell type of the innate immune system in the CNS; however, the mechanisms that control the activation of microglia are widely unknown. We systematically explored microglial activation and functional microglia-neuron interactions in organotypic hippocampal slice cultures, i.e., postnatal cortical tissue that lacks adaptive immunity. We applied electrophysiological recordings of local field potential and extracellular K+ concentration, immunohistochemistry, design-based stereology, morphometry, Sholl analysis, and biochemical analyses. We show that chronic activation with either bacterial lipopolysaccharide through Toll-like receptor 4 (TLR4) or leukocyte cytokine IFN-γ induces reactive phenotypes in microglia associated with morphological changes, population expansion, CD11b and CD68 up-regulation, and proinflammatory cytokine (IL-1β, TNF-α, IL-6) and nitric oxide (NO) release. Notably, these reactive phenotypes only moderately alter intrinsic neuronal excitability and gamma oscillations (30-100 Hz), which emerge from precise synaptic communication of glutamatergic pyramidal cells and fast-spiking, parvalbumin-positive GABAergic interneurons, in local hippocampal networks. Short-term synaptic plasticity and extracellular potassium homeostasis during neural excitation, also reflecting astrocyte function, are unaffected. In contrast, the coactivation of TLR4 and IFN-γ receptors results in neuronal dysfunction and death, caused mainly by enhanced microglial inducible nitric oxide synthase (iNOS) expression and NO release, because iNOS inhibition is neuroprotective. Thus, activation of TLR4 in microglia in situ requires concomitant IFN-γ receptor signaling from peripheral immune cells, such as T helper type 1 and natural killer cells, to unleash neurotoxicity and inflammation-induced neurodegeneration. Our findings provide crucial mechanistic insight into the complex process of microglia activation, with relevance to several neurologic and psychiatric disorders.
Im Titel ist "gamma" als griechischer Buchstabe dargestellt
First published December 22, 2015
Gesehen am 30.06.2020